Serum 25-hydroxyvitamin D as a predictive biomarker of clinical outcomes in patients with primary membranous nephropathy - Duan, Suyan; Chen, Si; Lu, Fang; Zhou, Meng; Jiang, Ling; Chen, Chen; Geng, Luhan; Sun, Rui; Xu, Yili; Huang, Zhimin; Zhang, Chengning; Zhang, Bo; et al. (Frontiers in Nutrition, 2023)
Background: Primary membranous nephropathy (PMN) is an immune-related disease with increased morbidity and the most common cause of adult nephrotic syndrome (NS). The serum 25-hydroxyvitamin D [25(OH)D)], a biomarker of Vitamin D (VD) status, tends to decline in patients with kidney disease. However, the relationship between 25(OH)D and PMN is still unclear. Therefore, this study aims to clarify the association between 25(OH)D and disease severity and therapy response of PMN. Methods: 490 biopsy-proven PMN participants from January 2017 to April 2022 were recruited at the First Affiliated Hospital of Nanjing Medical University. Correlations between baseline 25(OH)D and manifestations of nephrotic syndrome (NS) or seropositivity of anti-PLA2R Ab were confirmed by univariate and multivariate Logistic analysis. Spearman’s correlations were used to examine the associations between baseline 25(OH)D and other clinical parameters. In the follow-up cohort, Kaplan-Meier analysis was applied to assess remission outcomes among groups with low-medium-high levels of 25(OH)D. Furthermore, the independent risk factors of non-remission (NR) were explored by COX regression analysis. Results: At baseline, 25(OH)D was negatively related to 24h urinary protein and serum anti-PLA2R Ab. The lower level of baseline 25(OH)D was associated with an increased risk for the incidence of NS in PMN (model 2, OR 6.8, 95% CI 4.4, 10.7, P<0.001), and seropositivity of anti-PLA2R Ab (model 2, OR 2.4, 95% CI 1.6, 3.7, P<0.001). Furthermore, the lower level of 25(OH)D during follow-up was demonstrated as an independent risk factor for NR even after adjusting age, gender, MBP, 24h UP, serum anti-PLA2R Ab, serum albumin and serum C3 [25(OH)D (39.2-62.3 nmol/L): HR 4.90, 95% CI 1.02,23.53 P=0.047; 25(OH)D<39.2 nmol/L: HR 17.52, 95% CI 4.04, 76.03 P<0.001); v.s 25(OH)D≥62.3 nmol/L]. The Kaplan-Meier survival analysis also demonstrated that the higher level of follow-up 25(OH)D had a higher possibility of remission than the lower one (Log Rank test, P<0.001). Conclusions: Baseline 25(OH)D was significantly correlated with nephrotic proteinuria and seropositivity of anti-PLA2R Ab in PMN. As an independent risk factor for NR, a low level of 25(OH)D during follow-up might serve as a prognostic tool for sensitively identifying cases with a high probability of poor treatment response.